Adsorption of gold from waste mobile phones by biochar and activated carbon in gold iodized solution. (1st February 2021) - Zhou, Wanying; Liang, Huiting; Lu, Yuanye; Xu, He; Jiao, Yongli
Highlights: Offered a gold recovery technology from WPCBs. Leaching and adsorption processes were included. Compared the adsorption effect and conditions of activated carbon and biochar. The adsorption efficiencies of activated carbon and biochar were both ≥98%. Extended the application of biochar which achieved using waste to recover waste. Abstract: The application of laboratory-generated biochar and activated carbon adsorbents in gold iodized solution for the recycling of waste mobile phone printed circuit boards (WMPCBs) is investigated. This research aims to solve problems associated with the existing gold recovery technologies of WMPCBs. Currently, the disposal of WMPCBs is expensive, involves complex processes, and contributes to secondary pollution. In this study, laboratory-generated biochar is produced from corn straw, wheat straw, and wood chips by pyrolysis. The effects of factors on the adsorption efficiency are investigated, and the optimal operating conditions for biochar and activated carbon adsorption are determined. The following optimal parameters were found for activated carbon: temperature = 25 °C, particle size = 40–60 mesh, dosage = 0.05 g/10 mL, pH = 7, reaction time = 2 h, and oscillation frequency = 200 r/min. The adsorption efficiency reached 98.6%. For biochar, optimization involved: raw material from corn straw at a pyrolysis temperature = 700 °C, reaction time = 5 h, oscillation frequency = 200 r/min, pH = 3, dosage = 0.15 g/10 mL, and temperature = 50 °C. An adsorption efficiency of 98% was achieved. The two adsorbents were compared, and results demonstrated that the adsorption properties of the laboratory-generated biochar were slightly inferior to those of the activated carbon; however, they were similar. Biochar adsorption can reuse waste, which may not only solve the current problems related to WMPCB recycling, but can help to achieve a "win-win" situation of increased environmental protection and sustainable utilization of resources.